Територіальна громада як суб’єкт фінансових правовідносин - Добровінський, А. В.; Dobrovinskyi, A. V.; ORCID: http://orcid.org/0000-0002-7463-2292 (Юридичний електронний науковий фаховий журнал. - 2017. - №5. - С. 79-82, 2017)
Стаття присвячена актуальним питання правового забезпечення фінансових інтересів територіальних громад в Україні, які безпосередньо або через відповідні органи самоврядування беруть участь у фінансово-правових відносинах. Розглянуті напрями діяльності та засоби участі територіальної громади у фінансових правовідносинах регіону та запропоновані зміни до законодавства щодо повно важень громади.

The article is focused on the relevant issue of legal provision of financial activities of territorial communities, which, directly or through appropriate agencies of self-government, participate in financial and legal relations. The activities of territorial communities, aimed at mobilizing, distributing and spending financial resources in the area, require legislative regulation, since it significantly influences the needs of the inhabitants of the region. The budget powers of territorial communities as participants in public financial relations, as well as normatively-established system of local self-government rights in foreign countries and their implementation in a specific legal model of budget decentralization have been analysed. Regulated systems of local self-government rights in foreign countries and peculiarities of their implementation in a specific legal model of budget decentralization organization have been studied. The current Ukrainian legislation provides grounds for arguing that the domestic budget system is built in such a way that territorial communities evolved on the basis of the autonomy of local budgets, at the same time, there is not a wide range of tax powers to local self-government agencies. The very potential «to set local taxes and fees in accordance with the law» is limited by the legislator, as the only legislative agency and the economic realities of the existence of the population in Ukraine as a whole. The expediency of the participation of the population of administrative-territorial units in any way prohibited by law is to supervise and control the flow of cash in local budgets, at all its stages – the formation, distribution and use of funds from local budget. It is determined that the approval of the territorial community and local self-government agencies as participants in the financial and legal relations is the development and approval of the statutes of territorial communities by the inhabitants of the respective communities. The author has considered directions of activity and means of participation of the territorial community in the financial legal relations of the region, and has suggested amendments to the legislation on the extension of the powers of communities to resolve issues of financing of delegated state powers and socio-economic projects of regions.

Статья посвящена актуальным вопросам правового обеспечения финансовых интересов территориальных общин в Украине, которые непосредственно или через соответствующие органы самоуправления участвуют в финансово-правовых отношениях. Рассмотрены направления деятельности и средства участия территориальной общины в финансовых правоотношениях региона и предложены изменения в действующее законодательство, касающиеся полномочий общины.
Territorial community as a subject of financial legal relations
Добровінський, А. В. Територіальна громада як суб’єкт фінансових правовідносин [Електронний ресурс] / А.В. Добровінський // Юридичний електронний науковий фаховий журнал. - 2017. - № 5. - С. 79-82. - Режим доступу: http://www.lsej.org.ua/5_2017/5_2017.pdf
Keywords: територіальна громада; фінансові правовідносини; суб’єкт права; учасник правовідносин; бюджет місцевого самоврядування; статут територіальної громади; права та обов’язки територіальної громади; территориальная община; финансовые правоотношения; субъект права; участник правоотношений; бюджет местного самоуправления; устав территориальной общины; права и обязанности территориальной общины; territorial community; financial legal relations; subject of law; participant of legal relations; budget of local self-government; charter of the territorial community; rights and responsibilities of the territorial community; Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина